2022
DOI: 10.3389/fonc.2022.918016
|View full text |Cite
|
Sign up to set email alerts
|

“Surviving Discrimination by Pulling Together”: LGBTQI Cancer Patient and Carer Experiences of Minority Stress and Social Support

Abstract: BackgroundLesbian, gay, bisexual, transgender, queer and/or intersex (LGBTQI) people with cancer and their carers report poorer psychological outcomes than the general non-LGBTQI cancer population. There is growing acknowledgement that these health inequities can be explained by minority stress, which can be buffered by social support.Study AimTo examine subjective experiences of minority stress and social support for LGBTQI people with cancer and their carers, drawing on qualitative findings from the Out with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 87 publications
0
27
0
Order By: Relevance
“…These findings confirm previous reports of higher levels of societal discrimination ( 108 ) and discrimination in health care ( 109 ) reported by TGD people compared with other SGM groups. This is an explanation for higher rates of distress found in TGD populations outside of the context of cancer ( 56 , 110 ), and impacts upon experiences of cancer survivorship and interactions with health care professionals ( 26 , 60 ). In previous research, TGD people of color, and those who identify as LBQ, are at highest risk of discrimination, harassment and violence ( 111 , 112 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings confirm previous reports of higher levels of societal discrimination ( 108 ) and discrimination in health care ( 109 ) reported by TGD people compared with other SGM groups. This is an explanation for higher rates of distress found in TGD populations outside of the context of cancer ( 56 , 110 ), and impacts upon experiences of cancer survivorship and interactions with health care professionals ( 26 , 60 ). In previous research, TGD people of color, and those who identify as LBQ, are at highest risk of discrimination, harassment and violence ( 111 , 112 ).…”
Section: Discussionmentioning
confidence: 99%
“…LGBT people living in rural areas of the USA also report high rates of minority stress ( 77 ) and difficulties in interactions with health care providers ( 132 ). In the qualitative arm of the Out with Cancer Study , some participants living in a rural or regional area reported social isolation and social stigma ( 60 ), whereas others reported high levels of community and health care practitioner support due to living in a “rural, small-town area where everyone knows everyone” and which contributed to “being respected” ( 26 ). There needs to be further investigation of LGBTQI cancer survivorship and care outside of urban areas, in order to understand potential health disparities experienced by rural and urban LGBTQI cancer survivors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations